Does environmental archaeology need an ethical promise?. Issue 4 (7th August 2016) - Riede, Felix; Andersen, Per; Price, Neil
ABSTRACT: Environmental catastrophes represent profound challenges faced by societies today. Numerous scholars in the climate sciences and the humanities have argued for a greater ethical engagement with these pressing issues. At the same time, several disciplines concerned with hazards are moving towards formalized ethical codes or promises that not only guide the dissemination of data but oblige scientists to relate to fundamentally political issues. This article couples a survey of the recent environmental ethics literature with two case studies of how past natural hazards have affected vulnerable societies in Europe's prehistory. We ask whether cases of past calamities and their societal effects should play a greater role in public debates and whether archaeologists working with past environmental hazards should be more outspoken in their ethical considerations. We offer no firm answers, but suggest that archaeologists engage with debates in human–environment relations at this interface between politics, public affairs and science.